2022
DOI: 10.3390/healthcare10122377
|View full text |Cite
|
Sign up to set email alerts
|

Completed Suicide Linked to the COVID-19 Pandemic by Using the Psychological Autopsy Method in Sibiu County, Romania: Case Series and Literature Review

Abstract: The COVID-19 pandemic is associated with suicide, as some data suggests. Our study aims to investigate the emergence of eleven completed suicide cases suspected to be linked to the COVID-19 pandemic during the restrictive measures imposed by the Romanian government, and to identify the consequences of mental health, suicidal motivation, and behavioral changes. To this end, we analyzed the deceased’s medical records and applied the psychological autopsy method to the relatives/caregivers of the deceased for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…Forensic studies have demonstrated that the psychological autopsy represents a valuable tool for investigating COVID-19-related suicides. However, it is important to acknowledge limitations, such as the potential for interview bias and variations in the quality and quantity of information provided by subjects [30][31][32][33][34].…”
Section: Forensic Investigations Of Suicide Cases Due To Covid-19mentioning
confidence: 99%
“…Forensic studies have demonstrated that the psychological autopsy represents a valuable tool for investigating COVID-19-related suicides. However, it is important to acknowledge limitations, such as the potential for interview bias and variations in the quality and quantity of information provided by subjects [30][31][32][33][34].…”
Section: Forensic Investigations Of Suicide Cases Due To Covid-19mentioning
confidence: 99%